Urgensi Undang-Undang Perlindungan Data Pribadi Dalam Mengatasi Masalah Keamanan Data Penduduk - Diah Puspitasari; Izzatusholekha Izzatusholekha; Sintia Kartini Haniandaresta; Dalila Afif (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2023)
The purpose of this study is to analyze whether the existence of the Personal Data Protection Act makes the public feel comfortable with their privacy which is a human right, because there are many leaks of personal data which greatly disturb comfort and security. -The Personal Data Act has resolved the issue of personal data security or not. The research method used is the literature study method which is a method that is carried out by collecting library data, taking notes and reading, as well as managing research materials from previous studies and making direct observations. The results of public observations have full hopes that this personal data protection law can become their guarantee to protect personal data, the public hopes that with the tone of this Personal Data Law no one will dare to hack personal data illegally.